2021
DOI: 10.3390/ijerph18178965
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Renal Function and Plasma Metals Modified by EGFR and TNF-α Gene Polymorphisms in Metal Industrial Workers and General Population

Abstract: Exposure to metals may be associated with renal function impairment, but the effect modified by genetic polymorphisms was not considered in most studies. Epidermal growth factor receptor (EGFR) and tumor necrotic factor-α (TNF-α) play important roles in renal hemodynamics, and they have been reported to be associated with some renal diseases. The aim of our research is to explore whether genetic variations in EGFR and TNF-α have influence on renal function under exposure to various metals. This cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In 2021, a meta-analysis of 43 studies that analyzed the association of blood lead levels with renal function showed that high BUN is a valuable prognostic test for lead-associated kidney disease ( 129 ). A study on selenium from Taiwan and another on mercury from Colombia link the renal toxicity of these metals to genetic predisposition ( 130 , 131 ).…”
Section: Occupation and The Kidneymentioning
confidence: 99%
“…In 2021, a meta-analysis of 43 studies that analyzed the association of blood lead levels with renal function showed that high BUN is a valuable prognostic test for lead-associated kidney disease ( 129 ). A study on selenium from Taiwan and another on mercury from Colombia link the renal toxicity of these metals to genetic predisposition ( 130 , 131 ).…”
Section: Occupation and The Kidneymentioning
confidence: 99%
“…Previous animal studies have reported that treatment of Se can alleviate the nephrotoxicity that is induced by lead nitrate ( 7 ), cyclophosphamide ( 8 ), cisplatin ( 9 ), or streptozotocin ( 10 ), and Se deficiency has direct effects on renal injury ( 11 ). Population studies have also observed that plasma Se levels in nondialyzed CKD patients are lower than those of their healthy counterparts ( 12 , 13 ). However, longitudinal data on the association between selenium and renal function remain limited ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies focused on the analysis of As in urine, and less on the blood As. Whether urinary or blood As, many studies have shown that As exposure is inversely related to the glomerular filtration rate (GFR) or to the prevalence of proteinuria; however, the results were not consistent [ 5 , 6 , 7 ]. Furthermore, studies have revealed that chronic As exposure would lead to positive regulation of tumor necrosis factor- alpha (TNF-α) mRNA and other related factors, and then to atherosclerosis and skin lesions.…”
Section: Introductionmentioning
confidence: 99%